Self-Esteem antara Barat dan Islam: Perbandingan antara Coopersmith dan Fathi Yakan - Rusuli, Izzatur (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2020)
Self-esteem is an individual's evaluation of himself that he is valuable, meaningful, and capable. Having high self-esteem will bring happiness. This study aims to explore the concept of self-esteem sourced from the Qur'an, al-hadith, and thought of Muslim scholars then compares it with the concept of self-esteem from the West initiated by Coopersmith. This research is a research library using content analysis as a data analysis technique. The results showed that the concept of self-esteem in Islam is the essence of Surah Ali Imran verse 139 which states that true Muslims are individuals holding the highest degree. The comparison of self-esteem between the West and Islam, it is known that the aspects of self-esteem in the Western perspective include competence, significance, power, and virtue. Meanwhile, in Islam, aspects of self-esteem are the character of true Muslims such as having a safe belief, correct worship, good morals, building Islamic family and control of lust. The comparison between self-esteem in Western and Islamic concepts lies in its substance in which from a Western perspective, self-esteem starts from one's own efforts to have high self-esteem. Meanwhile, from an Islamic perspective, starts from being a true Muslim by internalizing the values of Islamic teachings in his life.